(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2018)
Demokirasi di negara-negara mayoritas muslim bergulir sejak berakhirnya perang dunia II, bukan hanya kalangan sekuler yang mengikuti Pemilu namun gerakan Islam seperti Ikhwanul Muslimin yang dicap radikal dan identik dengan terorisme juga mengambil bagian dalam pesta demokrasi di Mesir, Walau harus berhadapan dengan pemimpin otoriter dan mengalami berbagai macam teror, penyiksaan dan pembunuhan, gerakan Islam ini tetap istiqomah bahkan pada akhirnya mendapatkan kepercayaan masyarakat Mesir. Democratization in Muslim-majority countries has been running since the end of World War II, not just secularists who participated in the elections but Islamic movements like the Muslim Brotherhood stamped as radical and identical with terrorism also took part in the democratic party in Egypt. Despite having to deal with authoritarian leaders and experienced various kinds of terror, torture and murder, this Islamic movement still istiqomah even in the end get the trust of Egyptian society.